Vpliv skupin starih za samopomoč na kakovost življenja v lokalni skupnosti - Krajnc, Stanislava (Obzornik zdravstvene nege, 2005)
In the present article we try to show that community based self-help groups for elderly people can be considered an effective and useful approach in nursing care due to their positive impact on the elderly people's quality of life. Mechanisms of this impact are presented, as well as the concept of quality of life. On the basis of the described prospective study it was found out that community-based self-help groups positively affect the general estimation of the quality of life, as well as the perception of social relationships (the qualitative aspect of social contacts), of social participation (the quantitative aspect of social contacts) and the elderly people satisfaction with their health status. The impact of self help group onthe frequency of diseases, satisfaction with sight and hearing and satisfaction with their financial state have not been proved. The validity of our conclusions remains limited due to the identified methodological shortcomings of our study.
Keywords: Aged; Domača nega; gerontologija; Home Nursing; Kvaliteta življenja; Quality Of Life; Samopomoč, skupine; Self-Help Groups; skupine za samopomoč; Starostniki; zdravstvena nega